Pressure, state, response model (P-E-R) for the classification of environmental indicators and water quality management case: Puyango Tumbes river basin - Pandia Fajardo, Elma Alcira (2016)
The Puyango-Tumbes river basin derives from the polluting sources located basically in its upper and middle part, which incorporate a considerable amount of heavy metals into the water and, to a greater extent, into the sediments. The main activities that generate pollutants and incorporate them into the Puyango-Tumbes river are mining in the towns of Portovelo and Zaruma in the province of El Oro, Ecuador, as well as the generation and discharge of solid waste and residual water from the towns. seated in the river. This situation has already generated some problems in the lower part of the basin, a Peruvian sector, where it contaminates the rice soils on the left bank of the Tumbes river and the Tumbes mangroves; damaging direct food sources of the population and putting human health at risk. Within the framework of the aforementioned, this project aims to classify environmental indicators and contribute to the management of the quality of the surface waters of the Puyango-Tumbes river basin, through the Pressure-State-Response (P-E-R) model. The study was carried out on the Peruvian side, evaluating the surface water management programs of the Puyango, Tumbes basin that influence the classification of environmental indicators in the Puyango-Tumbes river basin; in addition to the sewage discharge points, identifying possible causes of contamination. The results show that the Tumbes river basin has an Environmental Quality Index (EQI) of 22.97 and the Zarumilla river basin has an EQI of 61.51